1986
DOI: 10.1002/cne.902510408
|View full text |Cite
|
Sign up to set email alerts
|

Retinal crowding alters the morphology of alpha ganglion cells

Abstract: It has been hypothesized that the dendritic field size of individual retinal ganglion cells is regulated early in development by interactions among neighboring cells (Wässle and Reiman, Proc. R. Soc. Lond. B. 200:441-461, 1978). An opportunity to test this hypothesis is provided by the consequences of prenatal enucleation that results in an increased density of ganglion cells in the remaining retina (Chalupa et al., Neuroscience 12:1139-1146, 1984). In the present study we compared dendritic field diameters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 37 publications
3
43
0
Order By: Relevance
“…The same phenomenon has been reported in a rat episcleral vein cauterisation glaucoma model, suggesting that the increment of RGC soma size intrinsically linked to soma density was probably a compensatory response to cell loss (Ahmed et al, 2001). It is possible that the remaining RGCs are stimulated to occupy the vacated areas after RGC death, increasing their soma area and/or dendritic field, as described by other authors (Perry & Linden, 1982;Kirby & Chalupa, 1986). The similarities in glaucomatous changes in the minipig model of POAG and human POAG are necessary for the translation of an effective animal model to understand the human disease.…”
Section: Retinal Ganglion Cell Deathsupporting
confidence: 70%
“…The same phenomenon has been reported in a rat episcleral vein cauterisation glaucoma model, suggesting that the increment of RGC soma size intrinsically linked to soma density was probably a compensatory response to cell loss (Ahmed et al, 2001). It is possible that the remaining RGCs are stimulated to occupy the vacated areas after RGC death, increasing their soma area and/or dendritic field, as described by other authors (Perry & Linden, 1982;Kirby & Chalupa, 1986). The similarities in glaucomatous changes in the minipig model of POAG and human POAG are necessary for the translation of an effective animal model to understand the human disease.…”
Section: Retinal Ganglion Cell Deathsupporting
confidence: 70%
“…In live imaging during development, it was observed that RGC dendrites actively avoid growing near RGCs of the same type (Lohmann and Wong 2001), indicating the presence of a repulsive interaction. In agreement with this hypothesis, removing a few RGCs during a critical period leads to an expansion of dendrites into the open space (Eysel et al 1985;Kirby and Chalupa 1986;Perry and Linden 1982). These observations suggest that the spatial extent of processes is the result of an active dendritic growth restricted by homotypic interactions between cells.…”
Section: Discussionmentioning
confidence: 79%
“…Extensions containing only F-actin were defined as dendritic filopodia. Only isolated neurons were chosen for analysis, because cell-cell contacts can influence dendritic differentiation (38). The hippocampal culture contained less than 1% astrocytes, as determined with glial fibrillary acidic protein immunohistochemistry for astrocytes and ␤-tubulin III immunohistochemistry for neurons.…”
Section: Expression Of Gst-pak-cdc42/rac Interactive Binding (Crib) Dmentioning
confidence: 99%